P-Cu2S/n-Si Anisotype Heterojunction Solar Cell - Al-Hamdani Ali (Engineering and Technology Journal, 2005)
An extensive study is presented on photovoltaic devices fabricated by spray pyrolysis method using aqueous solution of CuCl2.2H₂O onto a-type silicon substrates. The condition of preparation has been optimized to get good photovoltaic characteristics, these include short circuit current Isc of (1.82mA) and open circuit voltage Voc of (0.31mv). The conversion efficiency of the solar cell is equal to (3%) and the fill factor is (0.44).